Socio-Demographic and Clinical Outcome of the Patients with Shoulder Pain - Kh Mohammad Ali; Mohammad Sakib Al Nahian; Shohel Ahmed; AM Anisul Islam; Md Mustafezur Rahman; Raka Islam; Md Atikul Aziz (Medicine Today, 2026)
Introduction with Objective: Shoulder pain is a common musculoskeletal presentation in the general practice which can lead to absenteeism from work, inability to perform social activities and serious economic hardship for affected individuals and their families. The aim of this study was to assess the socio-demographic and clinical outcome of the patients with shoulder pain in a tertiary care hospital in Bangladesh. Methods: This Prospective observational Study was carried out among 101 patients attending at the Department of Physical Medicine and Rehabilitation, Dhaka Medical College and Hospital (DMCH), Dhaka within the defined period from July 2021 to December 2021. Ethical clearance was obtained from the Ethical review committee of Dhaka Medical College Hospital. Purposive sampling was done according to availability of the patients. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20.1). Results: Majority of the patients (59.4%) were in 41-50 years age group where the mean age of the patients was 50.3 ± 7.9 years and 51 (50.5%) patients were male. Majority of the patients (45.5%) were housewives. Most of the patients (n=94, 93.1%) had normal body mass index. Majority of the patients (56.4%) had duration of pain for 1-3 months where the mean duration of pain of the patients was 3.9 ± 2.5 months. The mean pain score in VAS was 4.9 ± 1.1 where 47 patients (46.5%) had score from 3-4. Local tenderness was present in rotator cuff muscle in 88 (87.1%) patients while 65 (64.4%) had tenderness on Gleno-humeral joint. Majority of the patients (59.4%) had shoulder pain on right shoulder. Conclusion: Shoulder pain is more common in older people, with the peak prevalence occurring in people aged 41-50 years and more common in male. Obesity is a risk factor for shoulder pain. Recognizing high-risk patients can help physicians for counseling them and recommend strategies for prevention. Medicine Today 2026, Vol.38 (1): 93-95